The flavor of place: Examining the impact of authentic local cuisine on tourist satisfaction and destination loyalty - Dias, Á.; Posheliuznaia, A. (International Journal of Sociology of Agriculture and Food, 2025)
This research examines the impact of authentic local cuisine on tourist satisfaction and revisit intention, with a focus on the mediating roles of destination image and destination branding. Utilizing a conceptual model and partial least squares structural equation modeling (PLS-SEM), this study analyzes data from 203 tourists. The findings reveal that authentic local cuisine significantly and positively influences tourist satisfaction, both directly and indirectly through destination image and destination branding. Furthermore, tourist satisfaction is identified as the most critical factor influencing revisit intention. The study provides valuable insights for destination marketers and policymakers, highlighting the competitive advantage of leveraging authentic cuisine as an effective branding strategy and offering practical steps to enhance tourist satisfaction and revisit intention.